Historia Słowenii oczami Polaka. O przekładach literatury słoweńskiej Joanny Pomorskiej - Cieślar, Joanna (Przekłady Literatur Słowiańskich, 2016)
The History of Slovenia in a Polish perspective. Slovenian literature as translated by Joanna Pomorska The article deals with the topic of translator’s choices while investigating the case of the translation of Drago Jančar’s book, Terra incognita, translated in Poland by Joanna Pomorska. This article is based on the theory of tropes by Hayden White, whose research is directly related to the historiography, and points out to the trap of objective or truly scientific history which, in fact, cannot exist. The same also applies to the essays that include some threads of history, such as Jančar’s essays concerning Slovenian history, analyzed not only in the Slovenian, but also in Yugoslavian and even European context. The image of history in his works is built on the remarkable way, where prevails the irony arising from the specific argument on the wheel of history. This unique perspective cannot be retained in the translation, where the translator must take into account a Polish reader’s limited knowledge about the Slovenian history. The author pays particular attention to illustrating the effects of translation strategies and its attitude towards the essay as a relay of history. She analyzes the translation choices on the lexical‑semantic level, and shows their impact on the perception of the text. Key words: essay, translation, history, Joanna Pomorska, Drago Jančar